2010
DOI: 10.5664/jcsm.27872
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Insomnia in Depressed Insomniacs: Effects on Health-related Quality of Life, Objective and Self-Reported Sleep, and Depression

Abstract: subscale (DLRF) of the Basis-32. Other measures included the Q-LES-Q, self-reported sleep, PSG, actigraphy, depression severity (HRSD) Results: At the end of randomized treatment, patients receiving ESZ had lower (better) DLRF scores (0.81 ± 0.64) than those receiving placebo (1.2 ± 0.72), p = 0.01. The effect size for DLRF was 0.62, indicating a moderate effect. An advantage for ESZ was also seen in other measures of HRQOL, and most assessments of antidepressant efficacy and sleep. Women reported better end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…Estimates of sleep latency, wake after sleep onset, and total sleep time will be obtained from the medium sensitivity setting at 30-second epochs, as described in our prior research. 76 We have previously reported that actigraphy tracks polysomnography reasonably-well in depressed insomniacs. 82 Actigraphic data will also be archived for potential future additional data analysis (functional analysis) as described above.…”
Section: E6 Measurement Of Suicidal Ideation and Behaviormentioning
confidence: 86%
See 1 more Smart Citation
“…Estimates of sleep latency, wake after sleep onset, and total sleep time will be obtained from the medium sensitivity setting at 30-second epochs, as described in our prior research. 76 We have previously reported that actigraphy tracks polysomnography reasonably-well in depressed insomniacs. 82 Actigraphic data will also be archived for potential future additional data analysis (functional analysis) as described above.…”
Section: E6 Measurement Of Suicidal Ideation and Behaviormentioning
confidence: 86%
“…ZOL/placebo will be stopped at the end of the treatment period as (1) sleep benefits may be continued in depressed insomniacs after a hypnotic is stopped, 75 and (2) most participants in our pilot study preferred stopping their hypnotic after 8 weeks of randomized treatment. 76 Participants will be referred for standard outpatient management at the end of 8 weeks of randomized care, with the option of receiving a SSRI prescription at the end of the trial until they re-enter usual care. We will also provide two weekly follow-up visits after discontinuation of ZOL to assess transition and provide continuity of care until the first care-as-usual visit.…”
Section: Change In Suicide Severity Index Inmentioning
confidence: 99%
“…When given daily diaries to complete, the rate of compliance rate has been reported to be as low as 11% (Stone, Shiffman, Schwartz, Broderick, & Hufford, 2003). Therefore, it is not surprising that McCall et al (2010) did not find any group by time interactions with self-report measures of sleep but found an interaction when using actigraphic measures of sleep. Furthermore, the reliance on self-report of Obstructive Sleep Apnea (OSA) symptoms may result in a largely under-diagnosed group of participants whose symptoms of OSA may interfere with both the effectiveness of an insomnia treatment and the accurate assessment and improvement of depressive symptoms (Waterman et al, 2016).…”
Section: Ta B L E 1 Characteristics Of Studies Of Insomnia Disorder Imentioning
confidence: 99%
“…There were also no differences in efficacy between women and men, and rebound insomnia and dose escalation were also absent. 36 Eszopiclone has been reported to be efficacious in treating patients with insomnia with comorbid diseases such as depression 37 and Parkinson's disease. 38 Compared to nonbenzodiazepine drugs, benzodiazepine drugs have more anxiolytic effects, which are dependent on the integrity of the α2 subunit, but postwithdrawal rebound, tolerance, and dependence are more important issues.…”
Section: Insomnia In the Elderlymentioning
confidence: 99%